Combinations of Previously-Approved Drugs Targeting Pseudomonas aeruginosa Development - Leung, Alexander (The Meducator, 2012)
Alexander Leung is a third year student in the Biomedical Sciences Specialization of the Bachelor of Health Sciences (Honours) Program. Under the supervision of Dr. Eric Brown, Alexander has been searching for novel thera-pies against the ubiquitous opportunistic pathogen, Pseudomonas aeruginosa. Herein, he introduces the bacterium and provides a primer on antibiotics with a particular focus on those used to combat P. aeruginosa infections. The focus of his research, conducted at the High Throughput Screening Laboratory in McMaster’s Centre for Microbial Chemical Biology, is to utilize high throughput screening to identify compounds that synergize with known antibiotics.